Light-Dependent Osmoregulation in Pea Stem Protoplasts. Photoreceptors, Tissue Specificity, Ion Relationships, and Physiological Implications - Long, Cheng (American Society of Plant Physiologists, 2001)
Light-induced changes in the volume of protoplasts bathed in a medium of constant osmolarity are useful indications of light-dependent cellular osmoregulation. With this in mind, we investigated the effect of light on the volume of protoplasts isolated from the elongating stems of pea (Pisum sativum) seedlings raised under red light. The protoplasts were isolated separately from epidermal peels and the remaining peeled stems. Under continuous red light, the protoplasts of peeled stems swelled steadily, but those of epidermal peels maintained a constant volume. Experiments employing far-red light and phytochrome-deficient mutants revealed that the observed swelling is a light-induced response mediated mainly by phytochromes A and B with a little greater contribution by phytochrome A. Protoplasts of epidermal peels and peeled stems shrank transiently in response to a pulse of blue light. The blue light responsiveness in this shrinking response, which itself is probably mediated by cryptochrome, is under the strict control of phytochromes A and B with equal contributions by these phytochromes. We suggest that the swelling response participates in the maintenance of high tissue tension of elongating stems and that the shrinking response is involved in stem growth inhibition. Other findings include the following: The swelling is caused by uptake of K(+) and Cl(−). The presence of Ca(2+) in the bathing medium is required for phytochrome signaling in the swelling response, but not in the response establishing blue light responsiveness. Phytochrome A mediates the two responses in a totally red/far-red light reversible manner, as does phytochrome B.